أهمية التسويق الفندقي في القطاع السياحي - بقدوربن عطية, سيليا (My University, 2021)
Tourisme is a adopty hôtelier in the développement of the national économes and also becouse of the impact on in corne and the balance of payements and is capacité to reduce inemployé and improuve touriste hôtelier aveas and mentalities national in and ividual due to the strategic importance of tourisme in the hôtelier is has become nécessairy to examine its status and development which means identifying all the fundamental problème that hinder the graoth of tourism hôtelier and diagnose the couses and this obtain positive resulte in light of the huge tourisme potential of the hôtelier and no doubt that the level of performance of the tourisme sector directly depends on the stability of the environnement and the culture of the community and high level of awareness and développements of modern infrastructure among the requirement for the upgrading of hôtelier to the wark of developing contries of tourism and for it to atract cousid arable internationnal market degment is the power of marketing and media
فندق LA BALE D'OR' "الخليج الذهبي " ولاية مستغانم
Keywords: marketing – marketing service – mix marketing service – hôtelier marketing